Manufacture and Characterization of Pandan Wangi (Pandanus amaryllifolius Roxb) Fiber-Based Composite Board with Epoxy Resin - Sinuhaji, Perdinan (Journal of Technomaterial Physics, 2020)
The manufacture and characterization of pandan wangi fiber-based compositeboards with epoxy resin using random fiber orientation method, fiber length 4 cm, withfiber composition in grams (0, 0.1, 0.2, 0.3, 0.4, 0.5), mechanical and physical testing hasbeen carried out. The results obtained a tensile strength value of 52.26 MPa, flexuralstrength 49.74 MPa, impact strength 30.6 kJ.mm-2, density 1.07 g.cm-3, and moisturecontent 2.05%. The results showed that the mechanical and physical properties that meetthe JIS A5905: 2003 standard are tensile strength > 0.4 MPa, bending strength > 32 MPa,density 0.3-1.3 g.cm-3, and moisture content 5-13 %. Therefore, pandan wangi fibercomposite with epoxy resin can be applied to car bumpers.